2015
DOI: 10.1111/ejn.12899
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting mirror visual feedback‐induced performance improvements in older adults

Abstract: Previous studies have indicated that age-related behavioral alterations are not irreversible but are subject to amelioration through specific training interventions. Both training paradigms and non-invasive brain stimulation (NIBS) can be used to modulate age-related brain alterations and thereby influence behavior. It has been shown that mirror visual feedback (MVF) during motor skill training improves performance of the trained and untrained hands in young adults. The question remains of whether MVF also imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 58 publications
4
27
0
2
Order By: Relevance
“…Similar results were seen in a study of anodal tDCS (1 mA, 20 min) over the M1 with a supraorbital return electrode (20 min, 1 mA) with regard to attention, discomfort and fatigue (Hoff et al, 2015). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aesupporting
confidence: 83%
See 1 more Smart Citation
“…Similar results were seen in a study of anodal tDCS (1 mA, 20 min) over the M1 with a supraorbital return electrode (20 min, 1 mA) with regard to attention, discomfort and fatigue (Hoff et al, 2015). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aesupporting
confidence: 83%
“…About one-third of the studies published until 2016 in aging populations reported no occurrence of tDCS-related AEs without giving details (Table 7). The most commonly reported AEs were typical tingling and itching that usually occurred when stimulation began but were also reported under sham conditions, where stimulation was applied only for a short duration at the beginning of the session (Boggio et al, 2010; Fertonani et al, 2014; Gandiga et al, 2006; Harty et al, 2014; Hoff et al, 2015; Holland et al, 2011; Learmonth et al, 2015; Manenti et al, 2013; Parikh and Cole, 2014; Sandrini et al, 2014, 2016). …”
Section: The Application Of Low Intensity Tes In Human Studies: Aementioning
confidence: 99%
“…In the present study, the effects of MVF were found in low mu, high mu, and low beta bands, which is in line with previous investigations conducted among healthy adults [22,24,32]. Moreover, we found that both protocols enhanced the MVF-induced ERD in the high mu and low beta bands, indicating that both TBS protocols delivered to the motor cortex could make the brain more receptive to MVF, which provide neurophysiological evidence to explain the behavioral bene ts from excitatory motor cortex stimulation on the observation-based motor learning [32,47,48]. However, we did not nd any signi cant difference between the two TBS protocols.…”
Section: Mvf-induced Erdsupporting
confidence: 91%
“…A series of studies have looked at online learning and adaptation effects over the life span (Goodwill, Reynolds, Daly, & Kidgell, 2013;Hardwick & Celnik, 2014;Hoff et al, 2015;Hummel et al, 2010;Zimerman et al, 2013). Hummel and colleagues (2010) investigated motor performance effects of tDCS using a crossover design in a cohort of older adults (Hummel et al, 2010).…”
Section: Online Motor Performance and Skill Learningmentioning
confidence: 99%